(untitled) (Homoeopathy for All, 2025)
Indigestion refers to sensation of pain, discomfort or burning in the upper abdominal region. The clinical term for indigestion is dyspepsia, derived from the Greek word “dyspeptos” where “dys” means “bad” or “difficult” and “peptos” means “to digest”. Indigestion is not a disease itself but rather a group of digestive symptoms, including belching, bloating, heartburn, nausea, and vomiting. Indigestion can be occasional or chronic in nature. Occasional indigestion is often linked to lifestyle factors while chronic indigestion is indicative of a more serious underlying condition requiring medical evaluation.